SPARKESX: Single-dish PARKES data sets for finding the uneXpected – a data challenge. Issue 4 (9th September 2022) - Yong, Suk Yee; Hobbs, George; Huynh, Minh T; Rolland, Vivien; Petersson, Lars; Norris, Ray P; Dai, Shi; Luo, Rui; Zic, Andrew
ABSTRACT: New classes of astronomical objects are often discovered serendipitously. The enormous data volumes produced by recent high-time resolution, radio-telescope surveys imply that efficient algorithms are required for a discovery. Such algorithms are usually tuned to detect specific, known sources. Existing data sets therefore likely contain unknown astronomical sources, which will remain undetected unless algorithms are developed that can detect a more diverse range of signals. We present the Single-dish PARKES data sets for finding the uneXpected (SPARKESX), a compilation of real and simulated high-time resolution observations. SPARKESX comprises three mock surveys from the Parkes ' Murriyang ' radio telescope. A broad selection of simulated and injected expected signals (such as pulsars and fast radio bursts), poorly characterized signals (plausible flare star signatures), and 'unknown unknowns' are generated for each survey. The goal of this challenge is to aid in the development of new algorithms that can detect a wide range of source types. We show how successful a typical pipeline based on the standard pulsar search software, presto, is at finding the injected signals. The data set is publicly available at https://doi.org/10.25919/fd4f-0g20 (Yong et al. 2022 ).